Optimized preparation of dithiocarboxylated polyethyleneimine-polyacrylamide and its Cu(Ⅱ) removal performance and mechanism - SANG Fangjuan; WANG Gang; WANG Xue; YANG Xiaomin (Gongye shui chuli)
Dithiocarboxylated polyethyleneimine-polyacrylamide〔DT(PEI-PAM)〕 was prepared by using polyacrylamide(PAM),sodium hydroxide(NaOH), sodium hypochlorite(NaClO), and carbon disulfide(CS2) as raw materials. The Cu(Ⅱ) removal in water samples by DT(PEI-PAM) was investigated as the target, and the optimal preparation conditions of DT(PEI-PAM) were determined by orthogonal experiments. The removal performance of DT(PEI-PAM) for Cu(Ⅱ) was investigated by using flocculation experiments, and the preparation mechanism and the removal mechanism for Cu(Ⅱ) with DT(PEI-PAM) were investigated by characterization means. The results showed that the intermediate polyethylenimide(PEI) was prepared under the optimal conditions as 1% of PAM concentration, 1:1:2 of n(PAM):n(NaClO):n(NaOH), 30 ℃ of reaction temperature, 120 min of reaction time, and 6.5 of pH in reaction medium. The final product DT(PEI-PAM) was prepared under the optimal conditions as 1:2:3 of reactant mass concentration ratio for PEI:CS2:NaOH, 25 ℃ of pre-reaction temperature, 40 min of pre-reaction time, 60 ℃ of main reaction temperature, and 120 min of main reaction time. The highest removal rate of Cu(Ⅱ) by DT(PEI-PAM) was 96.15% in water sample〔25 mg/L of Cu(Ⅱ) and pH 6.0〕. The infrared characterization and energy spectrum analysis showed that the dithiocarboxyl groups were successfully introduced in DT(PEI-PAM). The mechanism of DT(PEI-PAM) for Cu(Ⅱ) removal was mainly oxidation reduction and chelation precipitation, and the flocculation mechanism was mainly adsorption bridging and net sweep action.